Pengaruh Perubahan Kebijakan Moneter terhadap Kinerja Saham Perusahaan: Analisis Perspektif Hukum Dan Ekonomi - Hasan Pratama Putra; Fathan Elan Yuukhaa Mukhtarudin; Muhammad Miftahul Ikhsan (Journal of Innovative and Creativity, 2025)
This research aims to identify and analyze the impact of monetary policy changes on company stock performance. From an economic perspective, this study examines how policy instruments such as benchmark interest rates, open market operations, and exchange rates affect stock prices through transmission mechanisms. Meanwhile, from a legal perspective, this study highlights how regulations and the legal framework in the capital market can mediate or amplify these impacts, as well as the resulting legal implications for companies and investors. This research uses a qualitative-quantitative approach with case studies of companies listed on the stock exchange.The research findings show that contractionary monetary policy, such as interest rate hikes, tends to negatively impact stock performance by increasing borrowing costs and reducing purchasing power. Conversely, expansionary monetary policy can stimulate economic growth and drive up stock prices. From a legal perspective, strong regulations can provide investor protection, but they can also create new obstacles or opportunities for companies in responding to changes in monetary policy. The analysis reveals a complex dynamic between economic policy and the legal framework that impacts the capital market as a whole. The study concludes that changes in monetary policy are a crucial factor in determining company stock performance, and their impact is amplified or moderated by the prevailing legal framework. Synergy between monetary policy and capital market regulation is crucial for maintaining financial stability and protecting investors. These findings provide important insights for regulators, market participants, and investors in addressing changes in economic polic